2014
DOI: 10.5665/sleep.3336
|View full text |Cite
|
Sign up to set email alerts
|

Acute Sleep Deprivation Increases Serum Levels of Neuron-Specific Enolase (NSE) and S100 Calcium Binding Protein B (S-100B) in Healthy Young Men

Abstract: Future studies in which both serum and cerebrospinal fluid are sampled after sleep loss should elucidate whether the increase in serum neuron-specific enolase and S100 calcium binding protein B is primarily caused by neuronal damage, impaired blood brain barrier function, or is just a consequence of increased gene expression in non-neuronal cells, such as leukocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 20 publications
4
44
0
Order By: Relevance
“…The increased blood–brain barrier permeability during sleep loss may explain the findings by Benedict et al . (), regarding the presence of neuronal and glial proteins in plasma after acute sleep deprivation in humans (Benedict et al ., ). The prolonged blood–brain barrier hyperpermeability after sleep loss might underlie the effects of sleep loss in hippocampal physiology, such as decreased neurogenesis (Guzmán‐Marín et al ., : Mueller et al ., ), altered hippocampal neurochemistry (Mohammed et al ., ) and reduced hippocampal volume (Meerlo et al ., ; Novati et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The increased blood–brain barrier permeability during sleep loss may explain the findings by Benedict et al . (), regarding the presence of neuronal and glial proteins in plasma after acute sleep deprivation in humans (Benedict et al ., ). The prolonged blood–brain barrier hyperpermeability after sleep loss might underlie the effects of sleep loss in hippocampal physiology, such as decreased neurogenesis (Guzmán‐Marín et al ., : Mueller et al ., ), altered hippocampal neurochemistry (Mohammed et al ., ) and reduced hippocampal volume (Meerlo et al ., ; Novati et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This experiment was a component of a larger study investigating a variety of other measures related to sleep deprivation's impact on hunger levels and immune system functioning, and thus parts of the study have been reported previously . Data regarding ghrelin levels was also reported in a previous paper .…”
Section: Methodsmentioning
confidence: 99%
“…Mouse models of AD, PD, and HD pathology also exhibit sleep abnormalities (2124). Sleep deprivation increases cerebrospinal fluid markers of neuronal injury and alters plasma markers of inflammation in humans (25, 26), and induces the unfolded protein response in the brain of mice, indicating endoplasmic reticulum stress and potential neuronal injury (27). Thus, inadequate sleep could prime the brain for neurodegeneration by promoting processes such as inflammation and synaptic damage which exert pathogenic effects across diseases.…”
Section: Sleep and Neurodegenerationmentioning
confidence: 99%